Michelia Alba Flower Oil Components as Tyrosinase Inhibitors: In Silico Study - Paundra Rizky Pratama; Felysia Isman; Cici Muarifah; Wahida Annisa Ermadayanti; Arif Fadlan (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
Melanin is generally known as a protector of human skin against radiation. However, the excessive production of melanin induces hyperpigmentation and other skin disorders. Arbutin, kojic acid, and hydroquinone have been used as inhibitors for tyrosinase which involves the synthesis of melanin through melanogenesis, but they show adverse effects. This article reports the potential of methyl 2-methylbutyrate, β-pinene, limonene, 1,8-cineole, linalool, α-terpineol, geraniol, and β-phenyl ethylalcohol contained in the essential oils of Michelia alba as tyrosinase inhibitors by in silico study. The experiments were conducted through molecular docking against a human tyrosinase protein target (1BUG) followed by absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction. Geraniol, β-phenyl ethyl alcohol, α-terpineol, and limonene yielded better docking scores than hydroquinone. These four compounds and 1,8-cineole and β-pinene, showed lower docking scores than kojic acid. The compounds interacted with 1BUG through hydrogen bonding, Van der Walls, alkyl/π-alkyl interactions, and π-π stacking. ADMET analysis indicated that they were potential candidates for oral drugs.